(untitled) (AYUSHDHARA, 2025)
Amavata, a chronic inflammatory condition, arises from vitiation of Vata associated with Ama (metabolic toxins). The vitiated Vata circulates Ama through channels (Dhamanis) and localizes in Shleshma Sthana (joints, stomach, etc.), producing stiffness, swelling, and pain. In Ayurveda, management emphasizes Deepana, Pachana, Virechana, Snehapana and Basti. Pathya plays a crucial role in the management of Amavata. In contemporary science it is correlated with Rhematoid Arthritis (RA). As the disease progresses the symptoms verses and it may lead deformity. Objective: To evaluate the therapeutic effect of Panchakola Siddha Yavagu and Simhanada Guggulu in an Amavata patient. Methodology: A 34-year-old female presented with multiple joint pain (dominantly knees), morning stiffness, swelling, anorexia, and difficulty in ambulation. Laboratory reports revealed raised inflammatory markers. She was administered Panchakola Siddha Yavagu (250ml daily on empty stomach) and Simhanada Guggulu (500mg twice daily) for 14 days with dietary guidelines. Follow-up was done on the 15th and 30th day. Results: Remarkable improvements were observed, including reduced joint pain, stiffness, and swelling. ESR decreased from 80 to 40, CRP from 9 to 8, and RA factor from 23 to 20. Appetite and mobility improved notably, and by the 30th day the patient was asymptomatic. Discussion: Panchakola supports Deepana and Pachana, aiding Ama Pachana. Simhanada Guggulu combines Shodhana and Shamana effects, exhibiting strong anti-inflammatory and analgesic actions. The combined therapy reduced inflammatory markers and enhanced quality of life. Conclusion: The cost-effective and simple regimen of Panchakola Siddha Yavagu with Simhanada Guggulu proves highly effective in managing Amavata.